2005
DOI: 10.1093/humrep/deh773
|View full text |Cite
|
Sign up to set email alerts
|

Increased cystic fibrosis transmembrane conductance regulator (CFTR) expression in the human hydrosalpinx

Abstract: These results indicate that HSP epithelium undergoes epithelial transformation with elevated CFTR expression, which may lead to increased transepithelial electrolyte and fluid secretion resulting in HF formation. The present findings may lead to the development of new treatment strategies for infertile patients with HSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…The latter, in turn, induces an infective state termed ‘periodontitis’, which is characterized by bacteria‐induced inflammatory destruction of tooth‐supporting structures and the alveolar bone (Jin, 2008). The increased expression of CFTR in infections as observed in gingival tissues from the present study has also been reported in other tissues (Ajonuma et al, 2005a). Earlier studies have shown that some bacteria, such as Pseudomonas aeruginosa (Pier et al, 1996, 1997) and Salmonella typhi , (Pier et al, 1998) use CFTR as a receptor for their binding and uptake into epithelial cells.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The latter, in turn, induces an infective state termed ‘periodontitis’, which is characterized by bacteria‐induced inflammatory destruction of tooth‐supporting structures and the alveolar bone (Jin, 2008). The increased expression of CFTR in infections as observed in gingival tissues from the present study has also been reported in other tissues (Ajonuma et al, 2005a). Earlier studies have shown that some bacteria, such as Pseudomonas aeruginosa (Pier et al, 1996, 1997) and Salmonella typhi , (Pier et al, 1998) use CFTR as a receptor for their binding and uptake into epithelial cells.…”
Section: Discussionsupporting
confidence: 90%
“…The latter, in turn, induces an infective state termed 'periodontitis', which is characterized by bacteria-induced inflammatory destruction of tooth-supporting structures and the alveolar bone (Jin, 2008). The increased expression of CFTR in infections as observed in gingival tissues from the present study has also been reported in other tissues (Ajonuma et al, 2005a). Earlier studies have shown that some bacteria, such as Pseudomonas aeruginosa (Pier et al, 1996, Figure 3 Mean CFTR immunoreactive intensity in biopsies from periodontally healthy subjects and chronic periodontitis patients Staining intensity measurements were done using Image-Pro Plus version 6.3 (Media Cybernetics), which shows that CFTR immunoreactive intensity in the gingival biopsies from subjects with chronic periodontitis was significantly higher than those from healthy subjects (*P,0.05, Newman-Keuls test).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…By immunostaining, CFTR has been observed in the apical surface of uterine and oviduct epithelial cells involved in fluid secretion (Rochwerger and Buchwald 1993). In the Fallopian tubes, CFTR is localized specifically to the apical membrane of epithelial cells (Ajonuma et al 2005). CFTR immunostaining is also present in the apical membrane of fluid-secreting cells of the endocervix (SM Kreda, unpubl.).…”
Section: Cftr Expression In the Reproductive Organsmentioning
confidence: 99%
“…However, another possibility is that low-grade chronic infections in HSP may induce differentiation of epithelial cells leading to enhanced expression and/or down-regulation of some ion channels and transporters responsible for transepithelial transport causing a shift in the secretion and absorption balance of the uterine tube epithelium (Ajonuma et al, 2005). This low-grade, silent but chronic infection may be the reason for the reported early and increased rate of differentiation of cultured HSP epithelial cells from epithelial to fibroblast-like cells in vitro and reduced secretory vacuoles that we observed in our previous study (Ajonuma et al, 2003).…”
Section: Discussionmentioning
confidence: 99%